The effects of Al2O3 amount on the microstructure and properties of Fe-Cr matrix composites - Saidatulakmar, Shamsuddin; Shamsul Baharin, Jamaludin, Prof. Dr.; Zuhailawati, Hussain; Zainal Ariffin, Ahmad (Springer, 2011)
Link to publisher's homepage at www.springer.com